2008
DOI: 10.1080/00222340802216020
|View full text |Cite
|
Sign up to set email alerts
|

Transcrystallinity in a Polycarbonate(PC)/Polyethylene(PE) Blend Prepared by Gas-Assisted Injection Molding: A New Understanding of Its Formation Mechanism

Abstract: A PC/PE(20/80) blend was molded by gas-assisted injection molding and, after being etched, its crystalline morphology was investigated. Microscopy results indicate that transcrystallinity is favorably formed on the surface of the thinner PC fibrils. However, transcrystallinity cannot be observed on the PC droplets' surface. In addition, in the non-isothermal crystallization process, there was no transcrystallinity formed around the PC fibrils under the condition without shear. Combining the characteristics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…10). The transcrystalline regions were suggestive of deformation-induced crystallization [59], taking place during, or immediately after foam expansion, and hence to contribute to the overall structural integrity of foams at high temperatures as suggested previously. It follows that the equiaxed spherulites, which were generally dominant, were formed well after foam expansion in the relatively low cooling rate regime at 110°C and below.…”
Section: Crystallization Behaviormentioning
confidence: 74%
“…10). The transcrystalline regions were suggestive of deformation-induced crystallization [59], taking place during, or immediately after foam expansion, and hence to contribute to the overall structural integrity of foams at high temperatures as suggested previously. It follows that the equiaxed spherulites, which were generally dominant, were formed well after foam expansion in the relatively low cooling rate regime at 110°C and below.…”
Section: Crystallization Behaviormentioning
confidence: 74%
“…As a result, close-knit nuclei impede the full extension of the spherulites, which are then compelled to grow in one direction that is perpendicular to the fiber axis. [33][34][35] In the skin and sub-skin regions, polymer chains orient along the PC microfibrils and then a high density of active nuclei form on the surface of PC microfibrils in the presence of an intense shear field caused by the melt second flow. A part of the active nuclei induce an epitaxial growth of crystallites in folded chains and finally form a few b-transcrystalline superstructures, as shown in Fig.…”
Section: Crystal Structures Of the Pp/pc And Pp/pc/b-na Compositesmentioning
confidence: 99%
“…Compared with Figure 3(b) without shear at the same temperature, it was found that the shear force between the fiber and matrix could lead to the formation of transcrystallinity, which can produce better bonding between the matrix and fiber and improve the mechanical properties of composites. 22 This proved the benefits of high injection speed. However, according to Figure 7(c), the tensile strength increased and then decreased with the increasing injection speed.…”
Section: Resultsmentioning
confidence: 80%